2018
DOI: 10.11114/jets.v6i10.3451
|View full text |Cite
|
Sign up to set email alerts
|

Transformational Leadership and Job Satisfaction: The Case of Secondary Education Teachers in Greece

Abstract: In international literature there are many documented studies which have shown the relationship between leadership and job satisfaction. Specifically, transformational leadership is highly associated with this important and positive work attitude, that is, job satisfaction. The interpretation in a school context is that the director should operate as transformational leader so as to produce better educational outcomes through teachers' job satisfaction. In Greece, little empirical research has been done to inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
44
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(61 citation statements)
references
References 22 publications
7
44
0
10
Order By: Relevance
“…The result of the analysis proves that a crucial effect of Transformational Leadership exists on Job Satisfaction at the Faculty of Tarbiyah and Teacher Training of UIN Antasari Banjarmasin. That finding is confirmed by the study by Kouni, Koutsoukos, & Panta (2018), who also found that there is a robust effect of transformational leadership of the headmaster on the teachers' job satisfaction in Greece. Likewise, the results of the study conducted by Haddad, Badran, & Daood (2018) found the same results namely, transformational leadership influences the staffs' satisfaction on their job.…”
Section: The Effect Of Transformational Leadership and Work Disciplisupporting
confidence: 67%
“…The result of the analysis proves that a crucial effect of Transformational Leadership exists on Job Satisfaction at the Faculty of Tarbiyah and Teacher Training of UIN Antasari Banjarmasin. That finding is confirmed by the study by Kouni, Koutsoukos, & Panta (2018), who also found that there is a robust effect of transformational leadership of the headmaster on the teachers' job satisfaction in Greece. Likewise, the results of the study conducted by Haddad, Badran, & Daood (2018) found the same results namely, transformational leadership influences the staffs' satisfaction on their job.…”
Section: The Effect Of Transformational Leadership and Work Disciplisupporting
confidence: 67%
“…The significant role of school leaders in Greece is confirmed by the reported effects of leadership style on school climate, students' achievements, and teachers' job satisfaction [8,12,17,18]. The Greek educational system is characterized by a highly hierarchical structure with limited opportunities for creativeness and initiatives for school Principals.…”
Section: Introductionmentioning
confidence: 98%
“…School Principals may exhibit a range of leadership styles according to the national educational systems' policies, their personality traits, values, experiences and skills, as well as the particular issues and environmental parameters of their school unit [8][9][10][11][12][13][14]. In fact, effective leaders can adapt their leadership style depending on the context and situation of their school unit [8,12,13,[15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…It is clear that an organized and deliberate process of supervision and leadership can promote professional development and teacher satisfaction or be related to the results and progress of students (Ebrahimi et al, 2017;Zacharo et al, 2018). In this study, the experience of the shared leadership process between the university professor and the cooperating school teacher has a significant role in the enrichment of supervised practice.…”
Section: Discussionmentioning
confidence: 91%
“…It is also added that this theory seems to have a positive influence on the relationship with teacher job satisfaction and above all on the perception of their professional development. In turn, this degree of teacher satisfaction has a decisive effect on their lives as the investigation shows a strong correlation of this with the students' performance and progress (Zacharo, Marios, & Dimitra, 2018).…”
Section: Transformational Leadershipmentioning
confidence: 90%